Identification of Potential Biomarkers for Gut Barrier Failure in Broiler Chickens - Chen, Juxing; Tellez, Guillermo; Richards, James D.; Escobar, Jeffery (Frontiers in Veterinary Science, 2015)
The objective of the present study was to identify potential biomarkers for gut barrier failure in chickens. A total of 144 day-of-hatch Ross 308 male broiler chickens were housed in 24 battery cages with 6 chicks per cage. Cages were randomly assigned to either a control group (CON) or gut barrier failure (GBF) group. During the first 13 d, birds in CON or GBF groups were fed a common corn-soy starter diet. On d 14, CON chickens were switched to a corn grower diet and GBF chickens were switched to rye-wheat-barley grower diet. In addition, on d 21, GBF chickens were orally challenged with a coccidiosis vaccine. At d 21 and d 28, birds were weighed by cage and feed intake was recorded to calculate feed conversion ratio. At d 28, one chicken from each cage was euthanized to collect intestinal samples for morphometric analysis, blood for serum, and intestinal mucosa scrapings for gene expression. Overall performance and feed efficiency was severely affected (P < 0.05) by a GBF model when compared with CON group at d 21 and d 28. Duodenum of GBF birds had wider villi, longer crypt depth, and higher crypt depth/villi height ratio than CON birds. Similarly, GBF birds had longer crypt depth in jejunum and ileum when compared with CON birds. An increase (P <0.05) in serum endotoxin, α1-acid glycoprotein (AGP), as well as interleukin (IL)-8, IL-1β, transforming growth factor (TGF)-β4 and fatty-acid-binding protein (FABP) 6 mRNA levels were increased in GBF birds compared to CON; however, FABP2 mRNA levels were decreased (P <0.05) in GBF birds compared to CON. Occludin was numerically reduced by 24% (P = 0.107) and mucin 2 (MUC2) was reduced by 29 % (P = 0.088) in GBF birds compared to CON birds. The results from the present study suggest that serum endotoxin and AGP, as well as, gene expression of FABP2, FABP6, IL-8, IL-1β and TGF-β4 in mucosa may work as potential biomarkers for gut barrier health in chickens.